THE SIGNIFICANCE OF INTERROGATIVE SENTENCES WITHIN JOURNALISTIC WRITING - Turg’unova Fazilat Rustam qizi; Baxtiyorov Sunnatillo; Tojimurodova Ruxshona (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article delves into the significance of interrogative sentences in journalistic writing, examining how they function as potent instruments for captivating readers, stimulating critical thought, and effectively communicating information. The research explores different facets of interrogative sentences in journalism and their influence on engaging audiences.